Electrical Effect of Tabah Bamboo (Gigantochloa nigrociliata Buze-Kurz) Liquid Smoke Concentration and Cooking Temperature on Se’i Tuna Characteristics - Meranggi , Pande Putu Raditya Premananda; Kencana , Pande Ketut Diah; Wirawan , I Putu Surya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Tuna fish is a food that people like because it has rich nutrients so it requires continuous treatment to maintainabetter quality. Tomaintain a better qualityof tuna fishis using the liquid smoke method. The application of liquid smoke has many advantages among othermethods because itseasy application, givingthe product distinctive characteristics in the form ofa more attractive appearance, aroma, texture, taste, and does not pollute the environment. The liquid smoke wasused from tabah bamboo (Gigantochloa nigrociliata Buse-Kurz). This study aims to determine the effect of the concentration of liquid bamboo smoke and cooking temperature on the characteristics of Se'i Tuna. The methodused wasa factorial completely randomized design with two factors. The firstfactor is the concentration of liquid smoke (consisting of 2%, 4%, and 6%) and thesecond factor was the cooking temperature (consisting of 80oC, 90oC, and 100oC). The best treatment combination wasat a concentration of 6% liquid smoke and acooking temperature of 100oC byheatingfor 4hours, the water content was50.46%, protein content 17%, pH 5.53, ash content 2.81%, appearance sensory test 8,07, flavor 8,73, taste 8,73, and texture 8,60.